Pedunculopontine Nucleus Degeneration Contributes to Both Motor and Non-Motor Symptoms of Parkinson’s Disease - Chambers, Nicole Elaine; Lanza, Kathryn; Bishop, Christopher (Frontiers in Pharmacology, 2020)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by hypokinetic motor features; however, patients also display non-motor symptoms like sleep disorders. The standard treatment for PD is dopamine replacement with L-DOPA; however, many symptoms, including gait deficits and sleep disorders are unresponsive to L-DOPA. Notably, these symptoms have been linked to aberrant activity in the pedunculopontine nucleus (PPN). Of late, clinical trials involving PPN deep brain stimulation (DBS) have been employed to alleviate gait deficits. Although preclinical evidence implicating PPN cholinergic neurons in gait dysfunction was initially promising, DBS trials fell short of expected outcomes. One reason for the failure of DBS may be that the PPN is a heterogenous nucleus that consists of GABAergic, cholinergic, and glutamatergic neurons that project to a diverse array of brain structures. Second, DBS trials may have been unsuccessful because PPN neurons are susceptible to mitochondrial dysfunction, lewy body pathology, and degeneration in PD. Therefore, pharmaceutical or gene-therapy strategies targeting specific PPN neuronal populations or projections could better alleviate intractable PD symptoms. Unfortunately, how PPN neuronal populations and their respective projections influence PD motor and nonmotor symptoms remains enigmatic. Herein we discuss normal cellular and neuroanatomical features of the PPN, the differential susceptibility of PPN neurons to PD-related insults, and we give an overview of literature suggesting a role for PPN neurons in motor and sleep deficits in PD. Finally, we identify future approaches directed towards the PPN for the treatment of PD motor and sleep symptoms.